Sedimentation engineering : processes, measurements, modeling, and practice - García, Marcelo H., 1959- (ASCE manuals and reports on engineering practice ; No. 110, 2008)
1- Overview of sedimentation engineering. 2- Sediment transport and morphodynamics. 3- Transport of gravel and sediment mixtures. 4- Fine-grained sediment transport. 5- Sediment transport measurements. 6- Fundamentals of fluvial geomorphology. 7- Streambank erosion and river width adjustment. 8- River meandering and channel stability. 9- Stream restoration. 10- Bridge scour evaluation. 11- Bridge-scour prevention and countermeasures. 12- Reservoir sedimentation. 13- Ice effectes on sediment transport in rivers. 14- Computational modeling of sedimentation processes. 15- Two-and three-dimensional numerical simulation of mobile-bed hydrodynamics ans sedimentation. 16- Turbulence models for sediment transport engineering. 17- Watershed sediment yield. 18- Engineering geomorphology. 19- Sedimentation hazards. 20- American sedimentation law and physical processes. 21- Contaminant processes in sediments. 22- Sediment oxygen demand (SOD) in rivers, lakes and estuaries. 23- Development and application of numerical models of sediment transport associated with dam removal .